1989
DOI: 10.1111/j.1365-2559.1989.tb01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptors in benign epithelial lesions and intraduct carcinomas of the breast: an immunohistological study

Abstract: We examined 198 breast lesions, representing commonly encountered benign epithelial proliferative disorders, lobular carcinoma in situ and intraduct carcinoma, immunohistologically for oestrogen receptors (ER). A mixture of three ER monoclonal antibodies--H222, D75 and D547--was used on sections of routinely processed and paraffin-embedded tissue blocks. Over 65% of the benign and malignant lesions showed some evidence of ER expression and significant staining was recorded by two observers in 28-31% of fibroad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
18
0
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 13 publications
7
18
0
2
Order By: Relevance
“…Our finding of a relatively lower frequency of ER expression in comedo and large cell DCIS as compared to small cell DCIS is consistent with three earlier studies (Barnes & Masood, 1990;Bur et al, 1992;Giri et al, 1989). Barnes and Masood (1990) (Ronay et al, 1990).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of a relatively lower frequency of ER expression in comedo and large cell DCIS as compared to small cell DCIS is consistent with three earlier studies (Barnes & Masood, 1990;Bur et al, 1992;Giri et al, 1989). Barnes and Masood (1990) (Ronay et al, 1990).…”
Section: Resultssupporting
confidence: 93%
“…Results of ER status in DCIS in the literature have often been described as a part of much larger series of symptomatic invasive breast tumours. Previous studies have indicated that positive ER status in DCIS is associated with certain morphological subtypes of in situ mammary carcinoma (Barnes & Masood, 1990;Bur et al, 1992;Giri et al, 1989).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, unlike the latter (Bartkova et al, 1990), we found pS2 to be present in both the comedo and non-comedo types. Interestingly, the frequency of ER staining of paraffin embedded DCIS cases has been reported (Giri et al, 1989) to be much greater in cribriform, papillary and solid types (>50%) as compared with comedo (<20%). This discordance between pS2 and ER staining, also reflected by our own ER results, suggests that pS2 expression may not be obligatorily linked to that of ER as originally envisaged (Rio et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…ER and the natural history of breast cancer Many studies have reported no correlation between ER status and axillary lymph node status (Maynard et al, 1978;Hahnel et al, 1979;Mason et al, 1983;Williams et al, 1987;Hawkins et al, 1987a (DCIS) have reported positivity in between 32% and 80% of tumours depending on the cut-off level chosen for positivity (Giri et al, 1989;Malafa et al, 1990;Bur et al, 1992;Pallis et al, 1992;Soomro et al, 1992;Poller et al, 1993;Wilbur and Barrows, 1993; Murphy et al, submitted). The positivity rates for DCIS are similar to reported rates for invasive breast cancer, which argues against phenotypic drift as tumours progress biologically from preinvasive to invasive carcinoma.…”
mentioning
confidence: 99%